The application of information theory to parcel sorting - Degerlund, B. R.; Pemberton, A. W. (College of Aeronautics, 1969)
The work on parcel sorting was originally suggested to the Materials Handling Research Unit by British Rail which is one of the sponsoring organisations contributing to the Research Fund. This work has also formed the subject of a research thesis, which has been used as the basis of this report. The student, Mr. B. R. Degerlund is therefore the main author, in co-operation with the staff of the Research Unit … [cont.].